'Ilm al-qira'at wa-atharuhu fi fahm al-Qur'an : dirasah tahliliyah - Hafiz Anuar bin Abdullah (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study examines the different approaches of 'Ilm al-Qirā'āt in understanding of al-Qur'ān and how they produce different effects which influence the stand of Muslim scholars and researchers towards their acceptance of this knowledge. This study aims to explain that the various ways of recitation or Qirā'āt could lead to the different meanings but not in contradiction with what al-Qur'ān meant, and to analyze the importance of this knowledge to a better understanding in modern tafsīr. This study relies upon deductive and analytic methodologies by analyzing all relevant data. The findings of this study showed that the differences in Qur'anic recitation do not lead to contradictory meanings even if there are many ways of recitation but it varies the meaning of the Qur'anic verses.